Educazione democratica, ricerca scientifica, impegno politico e femminismo attraverso la vita di Irène Joliot-Curie - Cariati, Raffaele (Chimica nella Scuola, 2025)
The communist sympathizer Irène Joliot-Curie received an offer to join the government from Léon Blum, after the victory of the Popular Front in the second round of the parliamentary elections on 3 May 1936. Irène Joliot-Curie, Nobel prize winner in Chemistry in 1935, based on the work of Marie and Pierre Curie, who isolated some natural radioactive elements, succeeded in transmuting certain elements (such as boron, aluminum and magnesium) into synthetic radioactive isotopes. It appears, therefore, as the most daring appointment of Léon Blum. Republican, secular, progressive, will pass, not without leaving a mark in the state undersecretariat for scientific research. Researchers in mathematics and science education often stress the current and urgent need for humanization of teaching practices by interfacing them with history, the environment and the narrative of how scientific research also shapes the formation of a scientific spirit that commits politically towards the construction of a common good for all society. Very often in the classroom, in the name of the god of presumed effectiveness, teaching is oriented mainly towards algorithmic practices and semiotic treatments. A transdisciplinary reflection on the biography of Irène Curie, understood as a pedagogy of choice and commitment, can be an opportunity to strengthen the positioning of the dissemination of chemical sciences in space, in the time and complex and heterogeneous system of democratic scientific education.